Effets De L’incorporation Du Son De Maïs A Différents Doses Sur Les Performances De Croissance Des Lapereaux Et La Rentabilité De L’élevage - Chlodulfe, Tchibozo Sélidji Vital; Hippolyte, Dossa Luc; Fédéric, Houndonougbo; Ivan, Koura Bossima; Marcel, Houinato Benjamin (European Scientific Journal, ESJ, 2017)
This study was conducted to evaluate the performance of rabbits fed with rations containing corn bran at different levels of incorporation. Three rations, R5, R11 and R16, were formulated with incorporation rates of corn bran of 5.5%, 11% and 16.5%, respectively. Ninety young rabbits of 5 weeks of age were used for the experiments. The fattening study lasted 8 weeks and that of digestibility lasted for 1 week. The findings showed that the ration with 5.5% maize bran showed the best growth performances (18 g/d) with the highest digestibility values of dry matter (67%) and cellulose (97%). The ration with 16.5% corn bran yields 17 g / d with a better digestibility of the crude protein (97%) and the highest efficiency index (2.40). The ration with 11% maize bran is the most expensive (1395 Fcfa/kg) and has intermediate characteristics to that of the other two. The ration R could be used by rabbit farmers in urban and peri-urban areas to improve animal zootechnical performances. Future studies should be focused on the digestive use of different nutrients in rabbits through an in vivo study.